2010
DOI: 10.1021/jf102313b
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids, Epicatechin-Dimethylgallate, and Rutin Interact with Buckwheat Starch Inhibiting Its Digestion by Amylase: Implications for the Decrease in Glycemic Index by Buckwheat Flour

Abstract: Glycemic indexes of bread made from mixtures of wheat flour and buckwheat flour are lower than those made from wheat flour. To discuss the mechanism of the buckwheat flour-dependent decrease in glycemic indexes, the formation of a starch-iodine complex and amylase-catalyzed digestion of starch were studied using buckwheat flour itself and buckwheat flour from which fatty acids, rutin, and proanthocyanidins including flavan-3-ols had been extracted. Absorbance due to the formation of a starch-iodine complex was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 47 publications
3
56
0
3
Order By: Relevance
“…The fatty acid profile will thus determine the qualitative composition of produced volatile compounds. Significant differences in contents of individual fatty acids depend on the chemical composition of grain, which is connected with the type of cereal, cultivar and soil conditions (Takahama and Hirota, 2010). Volatile compounds produced most frequently via enzymatic decomposition of lipids is a characteristic trait for a given grain, being the main component of the profile of chemical compounds, comprising the taste and aroma of a given grain (Baker et al, 2006).…”
Section: Fatty Acidsmentioning
confidence: 99%
“…The fatty acid profile will thus determine the qualitative composition of produced volatile compounds. Significant differences in contents of individual fatty acids depend on the chemical composition of grain, which is connected with the type of cereal, cultivar and soil conditions (Takahama and Hirota, 2010). Volatile compounds produced most frequently via enzymatic decomposition of lipids is a characteristic trait for a given grain, being the main component of the profile of chemical compounds, comprising the taste and aroma of a given grain (Baker et al, 2006).…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Fatty acids could bind to amylose to form starch-lipid complex and render the starch more resistant to amylase-catalyzed digestion. Synergistically, rutin and proanthocyanidins are reported to be inhibitors of a-amylase (Takahama & Hirota, 2010).…”
Section: Buckwheatmentioning
confidence: 99%
“…Buckwheat (Fagopyrum esculentum) is widely used as a constituent of foods such as noodles and bread blended with flour from other cereals (Takahama & Hirota, 2010). Lin, Liu, Yu, Lin, and Mau (2009) made breads by mixing 15% of buckwheat flour with 85% of wheat flour in the hope to develop functional foods for diabetic patient.…”
Section: Buckwheatmentioning
confidence: 99%
“…Fraction AH-6-III was found to contain oleic, linoleic, and linolenic acid, as well as minor amounts of palmitic acid. For instance, in a recent study on buckwheat starch, fatty acids were among the compounds that were found to inhibit buckwheat starch digestion by α-amylase (Takahama and Hirota 2010). Although less likely, it is also possible that minor amounts of triglycerides were not fully extracted by using acetone and ethyl acetate before the alkaline hydrolysis of the extraction residue or that they had been released in the starch digestion step and not completely removed before the alkaline hydrolysis.…”
Section: Resultsmentioning
confidence: 99%